Evaluation of the success of shock index and its derivatives in determining mortality in STEMI cases applied to emergency department - Yurtsever, Guner; Çakır, Adem; Bora, Ejder Saylav (The European Research Journal, 2023)
Objectives: The shock index (SI) and its derivatives play a crucial role in rapid prognosis and risk assessment, particularly in emergent scenarios like ST-segment elevation myocardial infarction (STEMI). Methods: This study was conducted as a single-centered retrospective. A total of 467 cases that met the study criteria with a confirmed STEMI diagnosis were included. The SI, modified SI (MSI), age SI (ASI), and age-modified SI (AMSI) scores of the cases were calculated and compared. In this study, p 0.05 was accepted as the statistical significance level. Results: Calculated scores were compared among cases meeting STEMI criteria. Mortal cases displayed significantly higher SI, MSI, ASI, and AMSI, as well as elevated heart rates and lowered SBP, DBP, and MAP values. ASI exhibited the highest predictive success for mortality (AUC: 0.802), followed by AMSI (AUC: 0.798). AMSI demonstrated superior significance in estimating major adverse cardiovascular events (MACE) (p < 0.001 for each parameter). Conclusions: ASI proved most effective in gauging mortality risk, while AMSI excelled in predicting MACE risk among SI derivatives. These indices hold promise for guiding patient triage and emergency care in STEMI cases, owing to their simplicity and predictive capacity.